High-Responsivity PEDOT:PSS/SnS2/MoS2Double-Heterostructure-Based Organic-Inorganic Broadband Photodetector - Dwivedi A.K.; Jit S.; Tripathi S. (My University, 2025)
This current article proposes an Al/tin disulfide (SnS2)/molybdenum disulfide (MoS2)/poly(3,4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS)/indium tin oxide (ITO) structure-based organic-inorganic broadband photodetector fabricated on an ITO-coated PET (ductile polyethylene terephthalate) substrate using low-cost sol-gel method. The PEDOT:PSS acts as the active material cum hole transport layer (HTL), while the SnS2 acts as the active material cum electron transport layer (ETL) in the device. The large band offset between MoS2 and SnS2 creates an efficient built-in electric field at the depletion region of MoS2/SnS2 heterojunction, which enhances the drifting of photogenerated carriers to improve the photocurrent of the proposed photodetector. At -1-V bias and 0.118- μW illumination, the proposed device showed a broad photoresponse with the maximum responsivity, detectivity, external quantum efficiency (EQE), and sensitivity of 548.26 A/W, 2.49× 1012 Jones, 1.94× 105%, and 5.44 at 350 nm; 1389.08 A/W, 6.31× 1012 Jones, 3.82× 105 %, and 13.80 at 450 nm; and 457.47 A/W, 2.07× 1012 Jones, 4.72× 104 %, and 4.54 at 1150 nm, respectively. The rise time of 67.10μs and recovery time of 80.27μs were obtained at 450-nm wavelength. The high responsivity and EQE beyond 100% are attributed to the trap-assisted photomultiplication (PM) phenomena due to defects in SnS2 of the active layer. © 1963-2012 IEEE.